Filamentous Non-albicans Candida Species Adhere to Candida albicans and Benefit From Dual Biofilm Growth - Pathirana, Ruvini U.; McCall, Andrew D.; Norris, Hannah L.; Edgerton, Mira (Frontiers in Microbiology, 2019)
Non-albicans Candida species (NACS) are often isolated along with Candida albicans in cases of oropharyngeal candidiasis. C. albicans readily forms biofilms in conjunction with other oral microbiota including both bacteria and yeast. Adhesion between species is important to the establishment of these mixed biofilms, but interactions between C. albicans and many NACS are not well characterized. We adapted a real-time flow biofilm model to study adhesion interactions and biofilm establishment in C. albicans and NACS in mono- and co-culture. Out of five NACS studied, only the filamenting species C. tropicalis and C. dubliniensis were capable of adhesion with C. albicans. Over the early phase (0-4 hours) of biofilm development, both mono- and co- culture followed similar kinetics of attachment and detachment events, indicating that initial biofilm formation is not influenced by inter-species interactions. However, the NACS showed a preference for inter-species cell-cell interactions with C. albicans, and at later time points (5-11 hours) we found that dual-species interactions impacted biofilm surface coverage. Dual-species biofilms of C. tropicalis and C. albicans grew more slowly than C. albicans alone, but achieved higher surface coverage than C. tropicalis alone. Biofilms of C. dubliniensis with C. albicans increased surface coverage more rapidly than either species alone. We conclude that dual culture biofilm of C. albicans with C. tropicalis or C. dubliniensis offers a growth advantage for both NACS. Furthermore, the growth and maintenance, but not initial establishment, of dual-species biofilms is likely facilitated by interspecies cell-cell adherence.